Microsoft Excel Training for Data Processing for Vocational High School Students - Jauharul Maknunah; Indah Dwi Mumpuni; Linda Suvi Rahmawati; Rahayu Widayanti (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Microsoft Excel as one of the programs owned by MicrosoftOffice is needed to support the needs of daily activities. Thisprogram is already familiar to students and college students.Their knowledge about the use of functions in Microsoft Excel isnot optimal, they still need additional knowledge about theiruse. On this basis, Microsoft Excel training was conducted. Thistraining is held for Vocational High School (SMK) students whoare participating in the Industrial Work Program. The methodsused in providing training are lectures, discussions, practicumsand evaluations. At the time of implementation, participantsimmediately did practical work by completing practice questionsin the form of cases. The training materials cover MicrosoftExcel theory, implementation of functions and graphing. Theresult of this training is that the participants have an increasedunderstanding and ability to process data using Microsoft Excel.The score achieved by participants as much as 87% got a scoreabove the minimum average that has been determined.